Indicator Film of Natural Coloring of Butterfly Pea (Clitoria ternatea L.) as Detection of Beef Damage : Indicator Film of Natural Coloring of Butterfly Pea (Clitoria ternatea L.) as Detection of Beef Damage - Inanpi Hidayati Sumiasih (International Journal of Applied Biology, 2022)
Beef is a food source with a high protein content that would be ideal for microbes to flourish. Microbes would reduce the quality of a product. Therefore, an indicator on smart packaging would be needed to detect the quality of a product. The indicator film in this study used butterfly pea flower extract which contains a natural coloring agent, anthocyanin. The objective of this study was to obtain the indicator film with the best concentration of PVA, chitosan, and butterfly pea flower extract as the natural dye, to study the response of indicator film color, pH, and thickness, to the beef pH and TVBN, and to calculate the total microbes as the determinant of the beef quality. The study consisted of three steps, namely, the extraction of butterfly pea flower, the making of indicator film, and the application of indicator film on beef packaging. The best indicator film was obtained with the formulation of PVA and chitosan of 20:80 with the addition of 5 ml of butterfly pea extract. The color change was from blue to yellowish-green with °hue of 137.81±19.31o. The thickness of indicator film in 48 hours of storage decreased from 0.171±0.042 to 0.136±0.043. The pH of beef increased after 8 hours of storage from 5.726±0.011 to 7.540±0.351. The TVBN of beef after 8 hours of storage had exceeded the threshold of 30.815±5,602 which indicates that it was not safe for consumption. The TPC of beef from the 8 hours of storage had exceeded the maximum number of 7.338±0.035 log CFU/g. Keyword: anthocyanin, butterfly pea extract, thickness, volatile bases